2015
DOI: 10.1038/pr.2015.229
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma and urinary nitrite after birth in premature infants at risk for necrotizing enterocolitis

Abstract: Background Plasma nitrite serves as a reservoir of nitric oxide (NO) bioactivity. Because nitrite ingestion is markedly lower in newborns than adults, we hypothesized plasma nitrite levels would be lower in newborns than in adults, and that infants diagnosed with necrotizing enterocolitis (NEC), a disease characterized by ischemia and bacterial invasion of intestinal walls, would have lower levels of circulating nitrite in the days prior to diagnosis. Methods Single blood and urine samples were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…We recently observed that concentrations of plasma nitrogen oxide species (nitrite, SNOs, and iron nitrosyls) decrease by nearly 70% within minutes after birth [27], a phenomenon observed in both humans and sheep. There is evidence that inadequate mesenteric blood flow may play a role in necrotizing enterocolitis, a disease with a mortality rate of around 24% in preterm infants [28].…”
Section: Resultsmentioning
confidence: 99%
“…We recently observed that concentrations of plasma nitrogen oxide species (nitrite, SNOs, and iron nitrosyls) decrease by nearly 70% within minutes after birth [27], a phenomenon observed in both humans and sheep. There is evidence that inadequate mesenteric blood flow may play a role in necrotizing enterocolitis, a disease with a mortality rate of around 24% in preterm infants [28].…”
Section: Resultsmentioning
confidence: 99%
“…In the context of broad investigations confirming the significant effects of nitric oxide (NO) and ET-1 on the physiology and pathology of vascular homeostasis 33,34 , the role of endothelial dysfunction markers in the pathogenesis of epithelial injury of the intestinal tract has not been investigated completely. According to the results of correlation analysis in the present study, we hypothesised that decreased ET-1 levels in peripheral blood were a precursor for systemic hypoperfusion and may alter the protective functions of the intestinal mucosa, manifesting as decreased serum MUC2 and faecal HBD2 concentrations and increased ITF concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, the plasma nitrite levels in fetal sheep fall immediately after umbilical cord ligation and initiation of pulmonary ventilation (more than 60% decrease in plasma nitrite levels within 15 min after birth) (Fig. 2) (33). In humans too, the plasma nitrite levels in neonates rapidly fall at birth (from 0.18 ± 0.02 to 0.08 ± 0.02 μmol/L) and remains lower than those in adults for the first few weeks of life (34).…”
Section: Postnatal Decrease In Plasma Nitrite Levelsmentioning
confidence: 99%
“…In humans too, the plasma nitrite levels in neonates rapidly fall at birth (from 0.18 ± 0.02 to 0.08 ± 0.02 μmol/L) and remains lower than those in adults for the first few weeks of life (34). This may be associated with dramatic circulatory changes from the placental to pulmonary circulation at birth (33,34). Several reasons may account for this physiological decrease in plasma nitrite levels.…”
Section: Postnatal Decrease In Plasma Nitrite Levelsmentioning
confidence: 99%